The doublespeak discourse of the race disparity audit: an example of the White racial frame in institutional operation. Issue 1 (2nd January 2023) - Smith, Heather J.
ABSTRACT: The Race Disparity Audit (RDA) was published in 2017 by the then Conservative government of the UK. The proclaimed aims were to 'reveal racial disparities and to help end the injustices that many people experience'. This paper adopts a critical discourse analysis approach to analysing the RDA and associated webpages, to critically examine the government's purported aims. The linguistic analysis reveals a pernicious form of political doublespeak which effects a maintenance of the status quo. In excluding racism as a cause of disparities, the audit acts to de-legitimise anti-racism as part of the solution, thereby preventing actions with the potential to end racial injustices. The analysis is explained by reference to Feagin's (2013. The White racial frame. Centuries of racial framing and counter-framing (2nd ed.). New York, NY: Routledge) White racial frame in institutional operation. The paper concludes by exposing the ramifications of this for future policy development by reference to an education policy development borne from the RDA.